Contemporaneous phreatomagmatic and effusive activity along the Hverfjall eruptive fissure, north Iceland: Eruption chronology and resulting deposits - Mattsson, Hannes B.; Höskuldsson, Ármann (Journal of Volcanology and Geothermal Research, 2011)
ISSN:0377-0273 ISSN:1872-6097